Facile and shape-controlled electrochemical synthesis of gold nanocrystals by changing water contents in deep eutectic solvents and their electrocatalytic activity. Issue 11 (21st January 2016) - Li, Aoqi; Chen, Yujuan; Zhuo, Kelei; Wang, Congyue; Wang, Chunfeng; Wang, Jianji
Abstract : Au NCs with different morphologies were synthesized in DESs by changing water contents, and used as electrocatalysts for ethanol electrooxidation. Abstract : A green, facile and shape-controlled method was developed to synthesize Au nanocrystals (NCs) with different morphologies in deep eutectic solvents (DESs) with different contents of water. The shape and structure of Au NCs were tuned by using different DESs, and/or by controlling the applied potential and the content of water. The resulting Au NCs exhibited a high electrocatalytic activity and poisoning-resistance for ethanol electrooxidation in alkaline media.